Data from: Non-linear effect of sea ice: Spectacled Eider survival declines at both extremes of the ice spectrum ... - Christie, Katherine S.; Hollmen, Tuula E.; Flint, Paul; Douglas, David (Dryad, 2018)
Understanding the relationship between environmental factors and vital rates is an important step in predicting a species’ response to environmental change. Species associated with sea ice are of particular concern because sea ice is projected to decrease rapidly in polar environments with continued levels of greenhouse gas emissions. The relationship between sea ice and the vital rates of the Spectacled Eider, a threatened species that breeds in Alaska and Russia and winters in the Bering Sea, appears to be complex. While severe ice can impede foraging for benthic prey, ice also suppresses wave action and provides a platform on which eiders roost, thereby reducing thermoregulation costs. We analyzed a 23-year mark-recapture dataset for Spectacled Eiders nesting on Kigigak Island in western Alaska, and tested survival models containing different ice and weather-related covariates. We found that much of the variation in eider survival could be explained by the number of days per year with >95% sea ice ... : Annual_ice_combProjected sea ice data (number of days with >95% sea ice cover and <15% sea ice cover) for the Spectacled Eider core wintering area. Data from Global Circulation Models were downloaded from archives of CMIP5 GCM outputs (see Table S3 for a list of models).Historical sea ice dataThis file contains observed sea ice concentrations extracted for the core SPEI wintering area from daily gridded (25 km resolution) estimates that were derived from passive microwave satellite imagery using the Bootstrap Algorithm and disseminated by the National Snow and Ice Data Center, Boulder, CO. Data Citations: (1) Comiso, J. C. 2017. Bootstrap Sea Ice Concentrations from Nimbus-7 SMMR and DMSP SSM/I-SSMIS, Version 3. Boulder, Colorado USA. NASA National Snow and Ice Data Center Distributed Active Archive Center. doi: https://doi.org/10.5067/7Q8HCCWS4I0R. (2) Cavalieri, D. J., C. L. Parkinson, P. Gloersen, and H. J. Zwally. 1996, updated yearly. Sea Ice Concentrations from Nimbus-7 SMMR and DMSP SSM/I-SSMIS ...